Intercombination transitions of the carbon-like isoelectronic sequence - 刘浩 蒋刚 胡峰 王传珂 王哲斌 杨家敏 (Chinese physics B, 2013)
Energy levels, wavelengths, transition rates, oscillator strengths, and lifetimes between the 2s22p23P1,2s22p23P2,and 2s2p35S2 levels of ions in the carbon-like （C-like） isoelectronic sequence （nuclear charges Z=7-92） are calculated in the valence and core-valence limits using the multiconfiguration Dirac–Fock method. The Breit interaction, quantum electrodynamics （QED）, and finite nuclear mass effects are taken into account in subsequent relativistic configuration-interaction calculations. The calculated energies and transition rates are compared with the critically evaluated experimental values and other recent calculated results. Our calculated data are in good agreement with these data.